English Language in the Context of Cultural Diplomacy - Pratama, Rifka (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2023)
In the context of inter-state diplomacy, the need for English language proficiency remains essential. This would likewise apply to the promotion of the nation's cultures in the interest of establishing and strengthening a diplomacy with other countries. The use of cultural aspects for diplomatic purposes here is referred to as cultural diplomacy. Culture becomes the main aspect to attract the attentions of the projected partnering countries. In this context, culture can take the form of drama and music performances, cultural seminars, painting exhibitions, and others. This article aims to explain the concept of cultural diplomacy and its relevance with the use of English as the medium of instruction. The data were collected through the library study. Meanwhile, the analysis is carried out within a qualitative research framework where the relevant theories and the data were interpreted and synthesized. The research is also characterized by the interdisciplinary approach covering the subjects of culture, linguistics, communication, and politics. The results of the analysis affirm that English plays a significant and strategic position in supporting the exercises of cultural diplomacy. This is also supported by the intensive as well as frequent use of the international language in various forms of cultural diplomacy.